Factors Causing Delays in BPJS Health Inpatient Claims at Dr. Harjono S Regional General Hospital in Ponorogo Regency - Ike Wahyu Septian; Dwi Nurjayanti (Institut Kesehatan Pelamonia, 2025)
Ike Wahyu Septian, 2025 “Factors Causing Pending BPJS Health Inpatient Claims At RSUD Dr. Harjono S, Ponorogo Regency.” Scientific Paper, Supervisor: Dwi Nurjayanti, S.ST., M.Kes. Study Program of Diploma III in Medical Record and Health Information, STIKES Buana Husada Ponorogo. Pending inpatient BPJS Health claims pose a financial and operational challenge for hospitals. At RSUD Dr. Harjono S Ponorogo, 228 pending claims were identified in November 2024 out of 1,335 total claims. This issue was caused by incomplete supporting documents, coding errors, and non-specific medical diagnoses and procedures. This study used a descriptive qualitative approach through observation and interviews. The sample consisted of four claims officers and 228 inpatient pending claim files. The sampling technique used was purposive sampling. Data were analyzed through data reduction, presentation, and conclusion drawing. The study revealed several contributing factors: (1) Man – lack of accuracy and training among staff; (2) Method – suboptimal claim procedures; (3) Material – incomplete supporting documents; (4) Machine – information system disruptions; and (5) Money – delayed claim payments. The primary causes of pending inpatient claims are incomplete medical documentation and inaccurate coding. Improvements are needed in staff training, claim procedures, and system integration between hospitals and BPJS Health.